Cloud-native data pipelines with Apache Kafka (O'Reilly Media, 2019)
"Gwen Shapira (Confluent) discusses how data engineering requirements have changed in a cloud native world and how the solutions have changed with them. She then shares architectural patterns that are commonly used to build cloud native data infrastructure and explains how they help you build flexible, scalable, and reliable pipelines to give your business visibility on all your data. This session was recorded at the 2019 O'Reilly Strata Data Conference in San Francisco."--Resource description page